Formulation and Characterization of Spray Hand Sanitizer from Cuttlefish Bone Chitosan (Sepia sp.) as an Antibacterial Agent - Rasyid, Febriyanti; Naiu, Asri Silvana; Mile, Lukman (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractHand hygiene is crucial to prevent infection, while repeated alcohol use risks disrupting the skin barrier. This study formulated a hand sanitizer spray based on cuttlefish bone chitosan and evaluated its physicochemical quality and antibacterial activity against Escherichia coli. Chitosan was isolated through deproteinization, demineralization, and deacetylation, resulting in a 30% yield, 5.23% moisture content, 3.36% ash content, and a 74.78% deacetylation degree. The study used a completely randomized design with chitosan concentrations of 5%, 10%, and 15%. Results were analyzed using ANOVA for pH, viscosity, and inhibition zone. Significant differences were further tested using DMRT at a 5% significance level. The results showed an increase in pH from 8.38 ± 0.10 to 9.26 ± 0.47, viscosity from 750 ± 250 cP to 4517 ± 680 cP, and inhibition zone from 9.07 ± 1.33 mm to 25.43 ± 3.96 mm. The 5% formula had the best spray comfort despite its low activity, the 15% formula produced the most significant inhibition but had high viscosity, while the 10% formula provided the best compromise with potent antibacterial activity and functional viscosity. The pH value at 10% was still above the ideal skin range of 4.5–6.5, so buffer optimization was necessary. These findings confirm the potential of cuttlefish bone chitosan as an effective and environmentally friendly non-alcoholic alternative when pH and rheology are tightly controlled.Keywords: cuttlefish bone chitosan, Escherichia coli, pH, spray hand sanitizer, viscosity AbstrakKebersihan tangan berperan penting dalam pencegahan infeksi, sementara penggunaan alkohol berulang berisiko mengganggu sawar kulit. Penelitian ini merumuskan spray hand sanitizer berbasis kitosan tulang sotong dan mengevaluasi mutu fisikokimia dan aktivitas antibakterinya terhadap Escherichia coli. Kitosan diisolasi melalui deproteinasi, demineralisasi, dan deasetilasi yang menghasilkan rendemen 30%, kadar air 5,23%, kadar abu 3,36%, dan derajat deasetilasi 74,78%. Penelitian menggunakan rancangan acak lengkap dengan perlakuan konsentrasi kitosan 5%, 10%, dan 15%. Hasil dianalisis dengan ANOVA pada parameter pH, viskositas, dan zona hambat. Perbedaan nyata diuji lanjut dengan DMRT pada taraf signifikansi 5%. Hasil menunjukkan pH meningkat 8,38 ± 0,10 hingga 9,26 ± 0,47, viskositas 750 ± 250 cP hingga 4517 ± 680 cP, dan zona hambat 9,07 ± 1,33 mm hingga 25,43 ± 3,96 mm. Formula 5% memiliki kenyamanan semprot terbaik meski aktivitasnya rendah, formula 15% menghasilkan hambatan terbesar namun viskositasnya tinggi, sedangkan formula 10% memberikan kompromi terbaik dengan aktivitas antibakteri kuat dan viskositas fungsional. Nilai pH pada 10% masih di atas rentang ideal kulit 4,5–6,5 sehingga optimasi penyangga diperlukan. Temuan ini menegaskan potensi kitosan tulang sotong sebagai alternatif non-alkohol yang efektif dan ramah lingkungan saat pH serta reologi dikendalikan ketat.Kata kunci: Escherichia coli, kitosan tulang sotong, pH, spray hand sanitizer, viskositas